Evaluasi dan Design Ulang Drainase Jalan Raya untuk Meningkatkan Kinerja Hidraulik dan Mengurangi Risiko Banjir Lokal (Lembaga Pengembangan Kinerja Dosen, 2026)
Urban development has resulted in an increase in impermeable surfaces, increasing the risk of runoff inundating the road network. This situation occurs in the drainage system on Jl. Letjend S. Parman, Jl. Emo Kurniaatmaja, and Jl. Pulau Banda, Pasirkareumbi Village, Subang Regency. This study aims to evaluate the hydraulic performance of existing channels and develop redesign guidelines to reduce the risk of local flooding. The methods used include hydrological analysis of daily maximum rainfall data from the Subang rainfall station, rainfall frequency analysis using the Generalized Extreme Value (GEV) distribution, Intensity-Duration-Frequency (IDF) curves, and hydrological and hydraulic simulations using the Storm Water Management Model (SWMM). Model parameters include sub catchment area, rainfall intensity, time of concentration, infiltration using the Curve Number method, channel dimensions, cross-sectional shape, channel material, and the Manning coefficient. The results indicate that the GEV distribution provides a good fit for determining design rainfall. Based on the typology of a metropolitan city and a catchment area of ​​26.04 ha, the modeling period is 2 to 5 years. The SWMM simulation results indicate that some channel segments have very high flow velocities, potentially causing scour, while other segments have very low velocities, potentially causing sedimentation. This confirms the need for evaluation and restructuring of channel dimensions and slopes to improve the hydraulic performance of road drainage and reduce localized flooding.